PENINGKATAN HASIL BELAJAR PKN TENTANG SUMPAH PEMUDA MELALUI MEDIA AUDIO VISUAL - Thohir; Mutoharoh, Ulul Azmiatul; Handayani, Monika (Prosiding Temu Ilmiah Nasional Guru, 2023)
The learning of Civic Education in Grade III of SDIT Nurul Fikri Sidoarjo has been somewhat monotonous, using the same method. This has resulted in students feeling bored, indifferent, and passive. The primary objective of this study is to optimize student engagement and improve learning outcomes through the effective utilization of audiovisual aids. The research was conducted in two improvement cycles, focusing on the topic of the Youth Pledge (Sumpah Pemuda). The research findings indicate an improvement in students' learning outcomes. In the Pre-Cycle, the students achieved an average score of 70.85. Then, in Cycle 1, the students' average score increased to 90.75, and in Cycle 2, it further improved to 94.50. Not only did the learning outcomes improve, but students' learning activities also showed enhancement. The utilization of visual media resulted in enhanced student involvement and academic achievements in the field of Civic Education among Grade III students at SDIT Nurul Fikri Sidoarjo.